Wizard para Autoria Gráfica de Documentos NCL com Templates - Mattos, Douglas Paulo de; Silva, Júlia Varanda da; Saade, Débora Christina Muchaluat (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2012)
Using the declarative approach, interactive applications for the Brazilian digital TV system are developed using NCL (Nested Context Language). Although declarative languages facilitate building interactive TV applications, the author needs to have at least a basic knowledge of NCL. This paper proposes a wizard tool to allow the authoring of NCL documents for those with no knowledge about NCL. The proposed tool uses composite templates built with the XTemplate 3.0 language, which specify generic structures for NCL programs. The wizard presents a graphical interface which has drag-and-drop support for filling template components with specific media content nodes chosen by the author, making the creation of interactive TV applications easier. To do so, such media nodes are stored in a repository that organizes them by type. Furthermore, the graphical editing of content anchors for continuous media nodes is also provided. This wizard tool is a new version of a plugin of the graphical authoring environment for digital TV programs called NEXT (NCL Editor Supporting XTemplate).